2016
DOI: 10.1093/infdis/jiw386
|View full text |Cite
|
Sign up to set email alerts
|

The Global RegulonsarARegulates β-Lactam Antibiotic Resistance in Methicillin-ResistantStaphylococcus aureusIn Vitro and in Endovascular Infections

Abstract: Background. The global regulator sarA modulates virulence of methicillin-resistant Staphylococcus aureus (MRSA) via regulation of principal virulence factors (eg, adhesins and toxins) and biofilm formation. Resistance of S. aureus strains to β-lactam antibiotics (eg, oxacillin) depends on the production of penicillin-binding protein 2a (PBP2a), encoded by mecA.Methods. In the present study, we investigated the impact of sarA on the phenotypic and genotypic characteristics of oxacillin resistance both in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 51 publications
12
63
0
Order By: Relevance
“…The mecA locus encodes penicillin-binding protein 2a (PBP2a) that confers β-lactam resistance in MRSA strains (24). In addition, recent studies have demonstrated that the global virulence gene regulator, sarA, can also modulate β-lactam resistance via both mecA- dependent and mecA -independent mechanisms (23). To investigate the influence of NaHCO 3 exposure on mecA and sarA gene expression, RNA was extracted from cells grown in media with and without NaHCO 3 in the absence or presence of ½ MIC of oxacillin (to maximally induce mecA expression).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mecA locus encodes penicillin-binding protein 2a (PBP2a) that confers β-lactam resistance in MRSA strains (24). In addition, recent studies have demonstrated that the global virulence gene regulator, sarA, can also modulate β-lactam resistance via both mecA- dependent and mecA -independent mechanisms (23). To investigate the influence of NaHCO 3 exposure on mecA and sarA gene expression, RNA was extracted from cells grown in media with and without NaHCO 3 in the absence or presence of ½ MIC of oxacillin (to maximally induce mecA expression).…”
Section: Resultsmentioning
confidence: 99%
“…It is unclear, however, if NaHCO 3 has a direct impact on mecA expression, or if altered mecA gene expression is mediated through repression of sarA or other global regulons. Recent studies have shown that deletion of sarA and sigB can reduce mecA expression (23); therefore NaHCO 3 may be altering mecA expression directly and/or through one or both of these global regulatory pathways. In addition, we observed the mecA and sarA expression levels were reduced by NaHCO 3 exposures, in both the presence or absence of oxacillin induction ( Figs 5A;B ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The suppression of ABC transporters was another mechanism of anti-biofilm by 12C-Rha since nine proteins (OpuC, CycB, PstC, PhnC, ZnuA, MtsA, MtsB, HrtA and BraD) mapped to ABC transporters were downregulated. Thus, related substrates such as osmoprotectant, arabinogalactan oligomer/ maltooligosaccharide, phosphate, phosphonate, iron/zinc/ manganese/copper, hemin and bacitracin could not be transported properly in biofilm cells, causing the disruption of S. aureus biofilms [28]. Moreover, the function of ZnuA and MtsA that is directly related with iron transportation should be emphasized because iron is important for biofilm development [29].…”
Section: Discussionmentioning
confidence: 99%